Valuation of Recreational Fishing in Situ Cipondoh Using Travel Cost Approach - Juwarin Pancawati; Saifullah Saifullah; Forcep Rio Indaryanto (Jurnal Perikanan dan Kelautan, 2016)
Situ Cipondoh is favorite location for the fisherman in Tangerang Regency andthe surrounding area. The aim of the research is to know characteristics andperception from the fisherman to Situ Cipondoh and economic value ofrecreational fishing in Situ Cipondoh. The research using primary data which iscollected by accidental sampling from 50 fisherman. Valuation of recreationalfishing in Situ Cipondoh using travel cost approach. Average respondent age are34 years old, graduate from Senior High School and earn money about2.000.000,00 IDR – 3.000.000,00 each month. They usually come alone and stayfor fishing about 6 hours and more. Significant factor that affect the number oftourists is the number of fish catched. Based on the calculation, value ofrecreational fishing in Situ Cipondoh estimated at 281.687.255,62 IDR perannum.